Hadith as an Epistemic Tradition: Toward a Dialogue between Classical Criticism and Modern Academic Inquiry - Mawaddah, Niswa; mahfuza, Hilya; Indriani, Syifa Farizkha; Paranginangin, Dinda Silvani (Dialogues in Qur’anic and Hadith Studies, 2026)
This article examines Hadith as an epistemic tradition and proposes a dialogical framework for relating classical Hadith criticism to modern academic inquiry. The study responds to a persistent methodological tension in Hadith studies: classical criticism has often been associated with authentication, transmission reliability, and normative authority, while modern academic inquiry has emphasized historicity, textual variation, social memory, and the formation of religious authority. Rather than treating these approaches as mutually exclusive, this article investigates how they may be placed into critical and non-reductive dialogue. Methodologically, the study employs a qualitative textual and conceptual design, combining close textual analysis, comparative methodological inquiry, and hermeneutical interpretation. Its primary sources include classical Hadith collections and methodological works such as Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, Sunan Abī Dāwūd, al-Risālah, Maʿrifat ʿUlūm al-Ḥadīth, al-Jarḥ wa al-Taʿdīl, al-ʿIlal, Nukhbat al-Fikar, Fatḥ al-Bārī, and al-Minhāj. The findings show that Hadith functioned not merely as a corpus of reports, but as a structured system of knowledge production involving transmission, validation, classification, criticism, and interpretation. Classical Hadith criticism operated as an internal epistemic practice, while modern inquiry reframes Hadith through questions of historicity, textual formation, and social authority. The article contributes to Hadith studies by formulating a dialogical model based on epistemic mapping, methodological translation, critical reciprocity, and contextual application, thereby moving beyond the binary of apologetic traditionalism and sceptical historicism.